In vitro generation of a ureteral organoid from pluripotent stem cells - Yutaro Ibi; Koichiro Miike; Tomoko Ohmori; Chen-Leng Cai; Shunsuke Tanigawa; Ryuichi Nishinakamura (Nature Communications)
Abstract The ureter is the outlet for urine produced by the kidney. Recent advances in stem cell biology have enabled the in vitro generation of kidney organoids from pluripotent stem cells (PSCs), but they lack the ureter, which hinders the smooth drainage of urine. By mimicking the in vivo developmental process of ureteral stromal progenitors (SPs) from the posterior intermediate mesoderm, we report here in vitro induction protocols for ureteral SPs from mouse and human PSCs. When the induced SPs were combined with ureteral epithelia derived from mouse embryos, the elongated, multilayered ureteral structure was reconstituted, exhibiting peristaltic constriction. Some of the pathological features associated with the loss of Tbx18/TBX18 in mice and humans can be modeled using induced SPs lacking functional TBX18. Furthermore, the ureter-like spherical organoids entirely derived from mouse and human PSCs can also be generated by combining the induced SPs and the epithelial progenitor, the ureteric bud. Therefore, our induction protocols for ureteral SPs will be useful for the elucidation of ureteral development and diseases, and will be an important step towards functional kidney organoids with urine flow.